New palynological data from the Devonian Villavicencio Formation, Precordillera of Mendoza, Argentina (Ameghiniana, 2012)
Abstract. New terrestrial and marine palynomorphs of the lower part of the Villavicencio Formation, San Isidro Creek, Precordillera of Mendoza, Argentina, are evaluated. The palynomorph assemblage is dominated by miospores, and also contains acritarchs and scarce chitinozoans. Different processing methods have been tested due to the poor preservation state of the palynomorphs. The new slides provided abundant and diverse palynomorphs and allowed the recognition of 13 miospore species and two acritarch species. This review suggests a late Pragian to early Emsian age, thus confirming and refining previous palynological dating. The miospore assemblage may be correlated with the upper part of the Ems Biozone, in terms of the Devonian miospore zonation of the Brazilian Amazon Basin. Palaeogeographically, acritarchs show perigondwanan affinities. In the light of this refined age determination, the stratigraphic and phytogeographic inferences for the Precordillera land plants should be reconsidered.Resumen. NUEVOS DATOS PALINOLÓGICOS DE LA FORMACIÓN VILLAVICENCIO, DEVÓNICO DE LA PRECORDILLERADE MENDOZA, ARGENTINA.Se analizan nuevas asociaciones de palinomorfos continentales y marinos, provenientes de la parte inferior de la Formación Villavicencio, en la Quebrada de San Isidro, Precordillera de Mendoza, Argentina. Las asociaciones contienen predominantemente mioesporas, acompañadas por acritarcos y escasos quitinozoos. Como resultado de nuevos procesamientos paleopalinológicos se obtuvo un gran número de microfósiles, lo que permitió identificar 13 especies de mioesporas y dos de acritarcos. La revisión de las asociaciones sugiere una edad praguiana tardía a emsiana temprana, confirmando y precisando los resultados palinológicos previos. La asociación de mioesporas puede ser correlacionada con la Zona de Intervalo (Ems), correspondiente a la biozonación definida para el Devónico de la cuenca del Amazonas, en Brasil. En lo referente a la paleogeografía, los acritarcos demuestran claras afinidades gondwánicas. Se considera que la asignación estratigráfica, así como la propuesta de una nueva unidad fitogeográfica para las plantas halladas en la parte inferior de la Formación Villavicencio, deben ser revisadas.